PENGEMBANGAN MEDIA EVALUASI PEMBELAJARAN BERUPA GAME BERBANTU APLIKASI CONSTRUCT 2 PADA MATERI HUKUM NEWTON - Yuliani, Tri; Suseno, Nyoto; Riswanto, Riswanto (Universitas Muhammadiyah Metro, 2021)
Abstract: The results of interviews with physics teachers at SMAN 1 Pekalongan that the media provided is very limited. The media in school are only pictures, props, and powerpoint. Lack of care in the props makes the props become dirty and damaged. The purpose of making media is: (1). Knowing media development (2). Know how to develop media. (3). Knowing student responses to media (4). Knowning the advantages and disadvantages of the media. This research was conducted using the 4D development model ( define, design, development, disseminate) according to Trianto (2011: 189). The results of the media expert test research received a percentage of 69% with eligible criteria, the result of the test of material experts with a percentage of 73,08% with eligible criteria. The results of the product trial are the student response questionnaire with a percentage of 80,55% with very good criteria. Presentation obtained from the three expert tests stated that the evaluation media of game application learning was 74,21% with eligible criteria. Based of the results of the research regarding the development of game application learning media, the media developed are suitable for use as learning media. Media shortages are limited question, the advantages are easy to use, in the form of game, and is offline. Suggestions for this product can be developed by more than one material, along with sample questions. Media must also be used with all OS and smartphone. Publish it more widely by placing it in the online application store and can be download for free.Keywords: Research And Development, Learning Evaluation Media In The Form Of Assisted Game Application Construct 2, Newton’s Law